2000
DOI: 10.1097/00004647-200008000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Endogenous Brain Superoxide Dismutase as a Potential Mechanism of Lipopolysaccharide-Induced Brain Ischemic Tolerance

Abstract: A low dose (0.5 mg/kg) of lipopolysaccharide (LPS), administered 72 hours before 60-minute middle cerebral artery occlusion, induced a delayed neuroprotection proven by the significant decrease (-35%) of brain infarct volume in comparison with control, whereas infarct volumes remained unchanged in rats treated 12, 24, or 168 hours before ischemia. This delayed neuroprotective effect of LPS was induced only with low doses (0.25 to 1 mg/kg), whereas this effect disappeared with a higher dose (2 mg/kg). The delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
100
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(113 citation statements)
references
References 33 publications
12
100
0
1
Order By: Relevance
“…However, it appears that the LPS dose used in these models may be a determinant in the observed degeneration. In fact, although high LPS doses may increase cytokines and oxidative stress, low doses of peripheral LPS have a neuroprotective effect (Bordet et al, 2000). This is consistent with our recent study in which we observed an increase in brain NGF and GSH levels 3 days after peripheral LPS treatment (Arsenijevic et al, 2007b;Hernadfalvi et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, it appears that the LPS dose used in these models may be a determinant in the observed degeneration. In fact, although high LPS doses may increase cytokines and oxidative stress, low doses of peripheral LPS have a neuroprotective effect (Bordet et al, 2000). This is consistent with our recent study in which we observed an increase in brain NGF and GSH levels 3 days after peripheral LPS treatment (Arsenijevic et al, 2007b;Hernadfalvi et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…Although both animal models and clinical studies showed that infections promote neuronal death following cerebral ischemic injury (Sacco, 2001;Emsley and Tyrrell, 2002), activation of the immune system can also result in neuroprotection (Bordet et al, 2000). In fact, the effect of infection on ischemic damage may largely depend on the regulation of reactive oxygen species by pro-inflammatory and anti-inflammatory cytokines as well as by the main antioxidant state regulators, namely superoxide dismutase (SOD) (Guegan et al, 1998;Murakami et al, 1998), glutathione (GSH) (Nicholls and Budd, 2000;Schulz et al, 2000;Droge, 2002), uncoupling protein-2 (UCP2) (Arsenijevic et al, 2000b;Mattiasson et al, 2003) and nerve growth factor (NGF) (Brodie, 1996;Guegan et al, 1999;Villoslada et al, 2000).…”
mentioning
confidence: 99%
“…Both the uncorrected and corrected infarct volumes in three isofluranetreated groups were smaller than those of the Control group (uncorrected volume 287.2 ± 90.3 mm 3 and corrected volume 217.3 ± 79.5 mm 3 ). A significant reduction was observed in the Isoflurane group (uncorrected volume 137.4 ± 84.8 mm 3 and corrected volume 106.5 ± 60.0 mm 3 ) and the Vehicle+Isoflurane group (uncorrected volume 138.0 ± 84.2 mm 3 and corrected volume 104.7 ± 60.9 mm 3 ), (P < 0.01). The infarct volumes of DPCPX+Isoflurane group (uncorrected volume 250.1 ± 102.8 mm 3 and corrected volume 191.0 ± 80.0 mm 3 ) were significantly larger than those of the Isoflurane and Vehicle+Isoflurane groups (P < 0.01).…”
Section: Resultsmentioning
confidence: 87%
“…A significant reduction was observed in the Isoflurane group (uncorrected volume 137.4 ± 84.8 mm 3 and corrected volume 106.5 ± 60.0 mm 3 ) and the Vehicle+Isoflurane group (uncorrected volume 138.0 ± 84.2 mm 3 and corrected volume 104.7 ± 60.9 mm 3 ), (P < 0.01). The infarct volumes of DPCPX+Isoflurane group (uncorrected volume 250.1 ± 102.8 mm 3 and corrected volume 191.0 ± 80.0 mm 3 ) were significantly larger than those of the Isoflurane and Vehicle+Isoflurane groups (P < 0.01). Eight-cyclopentyl-1,3-dipropulxanthine treatment without isoflurane preconditioning in the DPCPX group did not change the infarct volume compared with the Control group.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation